2019
DOI: 10.1111/ipd.12501
|View full text |Cite
|
Sign up to set email alerts
|

Maternal perception of the impact of anterior caries and its treatment on children: A qualitative study

Abstract: Background Qualitative studies could allow a more comprehensive understanding about the breadth of children's experiences and perspectives regarding the impact of dental caries treatment. Aim To assess parental perception about children's oral health‐related quality of life (OHRQoL) following the rehabilitation of carious primary anterior teeth. Methods A purposive sample of parents of preschool children attending a University Dental Clinic due to caries in primary anterior teeth was recruited. Qualitative ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The personal stories told by our participants further underlie the significant impacts felt by P/C and children as a result of dental caries, such as a child's capacity to function holistically in being pain free and being able to eat, sleep, and interact socially and the flow-on impacts on the family. Similar reports of child and family impacts of a child's inability to function and socially interact meaningfully and parental distress have been found in studies elsewhere [ 5 , 21 ]. In the Brazilian study parents reported impacts relating to pain on eating, mispronunciation of words, and not wanting to smile for photos and parental guilt.…”
Section: Discussionsupporting
confidence: 74%
“…The personal stories told by our participants further underlie the significant impacts felt by P/C and children as a result of dental caries, such as a child's capacity to function holistically in being pain free and being able to eat, sleep, and interact socially and the flow-on impacts on the family. Similar reports of child and family impacts of a child's inability to function and socially interact meaningfully and parental distress have been found in studies elsewhere [ 5 , 21 ]. In the Brazilian study parents reported impacts relating to pain on eating, mispronunciation of words, and not wanting to smile for photos and parental guilt.…”
Section: Discussionsupporting
confidence: 74%
“…Dental caries is a common chronic disease estimated to affect a quarter of U.S. children ages 2-5 years [1]. Five-times more common than asthma, dental caries is responsible for many emergency room visits, pain, suffering, missed school days [2], and poor oral health related quality of life [3] in the affected child with negative impacts on the quality of life of families [4].…”
Section: Introductionmentioning
confidence: 99%